(untitled) (Al-Qamar, 2022)
Iqbal’s thoughtful views has given a cosmetic sense to our knowledge. Iqbal explained the meaning of self. Iqbal also presented the philosophy of selflessness. The interrelationship between the individual and the nation is central part of this philosophy. According to Iqbal, development of an individual is not possible without commitment to the nation. Iqbal sheds light on the basic tenets of the Islamic nation. He declared Tawheed as the first pillar. Iqbal says that the wisdom has found its destination due to Tawheed. The second pillar is the Risalat. These two components play an important role in the training of workers for the expansion Islamic rules. Iqbal has strengthened his thinking with reference to Quranic verses and explains his thoughts by giving sub-headings. The study concluded that the promotion of Iqbal’s philosophy of selflessness is inevitable for the development and expansion of Islamic Rules.